1982
DOI: 10.2307/3586470
|View full text |Cite
|
Sign up to set email alerts
|

Literature in the ESL Classroom

Abstract: This paper examines the pros and cons of using literature in an ESL classroom. The author argues that if literary texts are to be used successfully in the classroom, they must be carefully selected and approached in a manner which promotes an aesthetic interaction between the reader and the text. The paper concludes with a specific example of how a literary text might be approached so as to foster this type of interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
0
4

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(138 citation statements)
references
References 9 publications
8
126
0
4
Order By: Relevance
“…In this respect, these findings of the present study relate to those of Sakthivel & Kavidha (2010) who lament that language acquisition is purely theoretical not application-oriented. In this respect, the findings of this study are also seconded by those of the study conducted by Mckay (1982) who expresses the same reservation regarding the role of literature in the teaching of grammar. In his study, he maintains that literature lacks contribution to the teaching of grammar.…”
Section: Achievement Testsupporting
confidence: 69%
“…In this respect, these findings of the present study relate to those of Sakthivel & Kavidha (2010) who lament that language acquisition is purely theoretical not application-oriented. In this respect, the findings of this study are also seconded by those of the study conducted by Mckay (1982) who expresses the same reservation regarding the role of literature in the teaching of grammar. In his study, he maintains that literature lacks contribution to the teaching of grammar.…”
Section: Achievement Testsupporting
confidence: 69%
“…In general, research has shown that literature is very beneficial in helping students acquire the four language skills (reading, writing, listening, and speaking) and vocabulary, grammar, and pronunciation, either as excellent resources for English teaching and learning materials (Elklic, ErGgen, Kayintu, & Karaca, 2011;Floris, 2004;Maley, 1989;McKay, 1982;Riverol, 1991;Turker, 1991;Yeasmin, Azad, & Ferdoush, 2011); a popular technique (Hişmanoğlu, 2005); or an effective source for increasing students' creativity and imagination (Daskalovska & Dimova, 2012), enhancing motivation (Sell, 2005;Vural, 2013), and promoting cultural awareness (Cruz, 2010). Some research has also focused on the particular approaches of teaching English through literature, such as using literary analysis (Van, 2009), taskbased-approach , integrated approach (Healy, 2010;Zyngier, 1994), and developing the three approaches put forward by Carter and Long (1991) (Bedi, 2011;Bibby and Mcllroy, 2013).…”
mentioning
confidence: 99%
“…In line with this, McKay (1982) argues that, in literary works, the rich context helps increase the awareness of the students about language use. Literary texts increase the learners' proficiency of integrated language learning because they give opportunities for the learner to utilize all macro and micro skills together.…”
Section: A Backgroundmentioning
confidence: 85%
“…The status and benefit of literature in language class is discussed by many scholars. Among these, (Lazar, 1993;McKay, 1982;Widdowson, 1984) put their arguments on essentiality of literature in language class as it is the way to facilitate the development of language proficiency as well as cultural awareness of the learners.…”
Section: Why Use Literary Materials In Language Teaching?mentioning
confidence: 99%